Knowledge as a socio-economic category - Kulić, Radivoje N. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
As а socio-economic category, knowledge presupposes an analysis from the perspective of different scientific fields and disciplines. The applicable methods and procedures, as well as the terminology which results in the continuous development of the content and depth of knowledge, are specific. In line with this development is the diversity of classifications of knowledge that is increasingly expressed not only in its socio-psychological and pedagogical, but also economical aspects and essence. This, precisely, means that as the presuppositions for comprehensive technological civilizational trends and changes, knowledge is not only a social, but also an economic resource that defines the competitiveness and the overall progress of countries and their national economies.